Real-world efficacy and safety of dolutegravir plus lamivudine versus tenofovir plus lamivudine and efavirenz in ART-naïve HIV-1-infected adults. Issue 42 (21st October 2022) - Li, Jin; Chen, Dabiao; Wen, Zhiwei; Du, Yanzhang; Huang, Zhanlian; Zhong, Huijun; Wang, Yanhao; Yin, Sichun
Abstract : Limited real-world data on dolutegravir (DTG) plus lamivudine (3TC) for HIV-1-infected individuals have been reported. This study aimed to evaluated the real-world efficacy and safety of DTG + 3TC in ART-naïve HIV-1-infected adults in China. This real-world prospective observational cohort study enrolled HIV-1-infected adults receiving ART initiation with DTG + 3TC (D3 group) or tenofovir plus lamivudine and efavirenz (TDF + 3TC + EFV, TLE group) with subgroups of low viral load (LVL, ≤500, 000 copies/mL) and high viral load (HVL, >500, 000 copies/mL) according to baseline HIV-1 RNA. Efficacy were assessed by proportion of virologic suppression, changes of CD4 + cell count and CD4/CD8 ratio, HIV-1 DNA decay, and safety by symptoms and changes of laboratory indicators at week 4, 12, 24, 36, and 48. Totally 45 participants in D3 group and 95 in TLE group were enrolled. The proportion of HIV RNA < 50 copies/mL were 48.7% (19/39), 84.6% (33/39), 100% (39/39), 100% (39/39) in D3-LVL subgroup at week 4, 12, 24, 48, compared with 1.3% (1/75), 14.7% (11/75), 86.7% (65/75), 96.0% (72/75) in TLE-LVL subgroup, with P < .05 at week 4, 12, and 36. The proportion were 0.0% (0/6), 66.7% (4/6), 83.3% (5/6), 100% (6/6) in D3-HVL subgroup compared with 0.0% (0/20), 5.0% (1/20), 85.0% (17/20), 100% (20/20) in TLE-HVL subgroup, with P < .05 at week 12. No virologic rebound was observed in D3 group. Mean change of CD4/CD8 ratio were higher in D3-LVL versus TLE-LVL subgroup at each scheduled visit ( P < .05), while CD4 + cell counts increased significantly in D3-HVL versus TLE-HVL subgroup at week 4 and 12 ( P < .05). Less complaint of dizziness, insomnia, dreaminess and amnesia, lower elevated level of triglyceride and higher elevated level of creatinine from baseline to week 48 were documented in D3 group ( P < .05). Total HIV-1 DNA decayed along with HIV-1 RNA after DTG + 3TC initiation in both D3-LVL and D3-HVL subgroups. DTG + 3TC achieved virological suppression more rapidly and stably versus TDF + 3TC + EFV in ART-naïve HIV-1-infected adults, with better immunological response and less adverse drug effect, and reduced total HIV-1 DNA effectively. DTG + 3TC is a potent regimen for ART-naïve individuals with HIV-1 infection.